Reflexos da aceleração do Tempo Social na Teoria do Gatekeeping - Feil, Bruna Eduarda Meinen (2024)
This research analyzes the Gatekeeping Theory. We consider Journalism as a social institution of Modernity (NEVEU, 2006), impacted by acceleration processes of Social Time (ROSA, 2019). Therefore, we formulated the following research question: what evidence of the acceleration of Social Time can be identified in the history of the Gatekeeping Theory, and how does this theory address the acceleration of Social Time to explain the transformations in the professional field over time? The main objective is to observe how the acceleration of Social Time can be recognized in the Gatekeeping Theory, considering its historicity, as well as to reflect on how the acceleration of Social Time resonates in the understandings about Journalism proposed by the Gatekeeping Theory. To operationalize the research, we are inspired by Michel Foucault's archaeology (2008), to build an illustrative timeline of the Gatekeeping Theory. The periodization spans from David Manning White’s seminal paper on Gatekeeping and Journalism (1950) to the present. By examining multiple texts, we identified two distinct periods. The first phase extends until the end of the 1980s and is characterized by the diffusion of the model proposed by the Gatekeeping Theory in the field of Journalism. The second phase began in 1990 and continues until 2022. This period is characterized by the emergence of specialized research areas and the critical examination of contemporary transformations in Journalism. The timeline contributed to the definition of our analysis corpus, consisting of a total of 13 papers that are references for understanding the transformations of the Gatekeeping Theory through time. To categorize the indicators of the acceleration of Social Time, we used the metaphors - 'Channel,' 'Gate,' and 'Force' - as analytical tools. The archaeological analysis that led to our timeline, combined with the use of metaphors as operational tools, allowed us to simultaneously perform a synchronic and diachronic reading of the texts selected to compose our analysis corpus. Marks of the process of acceleration of Social Time were identified in the Gatekeeping Theory with the support of the three metaphors. The 'Channel' metaphor predominantly represents elements of technical acceleration, while the 'Gate' metaphor embodies elements of social change acceleration and the pace of life. The 'Force' metaphor, being the most abstract, reflects the inherent inertia in the process of accelerating Social Time described by Rosa (2019).